Polyuridylated mRNA synthesized by a recombinant influenza virus is defective in nuclear export. - Poon, L; Fodor, E; Brownlee, G (2000)
The poly(A) tail of influenza virus mRNA is synthesized by reiterative copying of a U track near the 5' end of the virion RNA (vRNA) template by the viral RNA polymerase. We have engineered a novel influenza A/WSN/33 virus which contains a neuraminidase (NA) vRNA with its U track mutated into an A track. Instead of synthesizing poly(A)-tailed NA mRNA, this novel virus synthesizes poly(U)-tailed NA mRNA. In infected cells, most poly(U)-tailed NA mRNA was retained in the nucleus, while most control polyadenylated NA mRNA was transported to the cytoplasm. These results suggest that the poly(A) tail is important for efficient nuclear export of NA mRNA. The mutant virus produced a reduced amount of NA and showed an attenuated phenotype, suggesting that poly(A) signal mutants of this type might be useful as potential live attenuated virus vaccines. In addition, this virus mutant might provide a useful model to further elucidate the basic mechanisms of mRNA nuclear export.